2015
DOI: 10.1051/0004-6361/201425569
|View full text |Cite
|
Sign up to set email alerts
|

The impact of surface dynamo magnetic fields on the solar iron abundance

Abstract: Most chemical abundance determinations ignore that the solar photosphere is significantly magnetized by the ubiquitous presence of a small-scale magnetic field. A recent investigation has suggested that there should be a significant impact on the derived iron abundance, owing to the magnetically induced changes on the photospheric temperature and density structure (indirect effect). The three-dimensional (3D) photospheric models used in that investigation have non-zero net magnetic flux values and stem from ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…We note, that the mean temperature in the MHD snapshot models of Rempel (2014) and Vögler & Schüssler (2007) agree very well with the temperature of the 1D semi-empirical model MACKKL (Maltby et al 1986) based on observations of the continuum radiation. As a result, the absolute continuum intensities at different wavelengths computed in the 3D snapshot model of Rempel (2014) are consistent with those calculated in the MACKKL model (see Shchukina & Trujillo Bueno 2015). At heights above log 10 τ 5 > −0.5, the above-mentioned 3D MHD snapshot models are significantly cooler compared to the MACKKL model.…”
Section: Model Atmospheresupporting
confidence: 82%
“…We note, that the mean temperature in the MHD snapshot models of Rempel (2014) and Vögler & Schüssler (2007) agree very well with the temperature of the 1D semi-empirical model MACKKL (Maltby et al 1986) based on observations of the continuum radiation. As a result, the absolute continuum intensities at different wavelengths computed in the 3D snapshot model of Rempel (2014) are consistent with those calculated in the MACKKL model (see Shchukina & Trujillo Bueno 2015). At heights above log 10 τ 5 > −0.5, the above-mentioned 3D MHD snapshot models are significantly cooler compared to the MACKKL model.…”
Section: Model Atmospheresupporting
confidence: 82%
“…For the iron ions, we obtained N(Fe i)=-4.42±0.03 dex and N(Fe ii)=-4.46±0.02 dex, which again highlights the known problem of the measured difference between Fe i and Fe ii abundances obtained in the framework of the classical approach (see Holweger, Heise & Kock 1990, Shchukina & Trujillo 2015, Shchukina, Sukhorukov & Trujillo 2016. The abundances for the other elements (see the first column of Table 2) are in agreement with those in the literature (e.g.…”
Section: Solar Abundancesmentioning
confidence: 56%
“…In a subsequent paper Fabbian and Moreno-Insertis (2015) studied the case of the O i lines and again found that an abundance determination using non-magnetic models would lead to underestimates by a few to several centi-dex. Shchukina and Trujillo Bueno (2015) challenged the results of Fabbian et al by a study of Fe spectra from 3D models with and without magnetic fields assuming that the former are dominated by small-scale dynamo action (with the net magnetic flux being zero). Also for solar C, N, and O spectra the effects were found to be negligible (Shchukina et al 2016).…”
Section: Effects Of Magnetic Fieldsmentioning
confidence: 82%
“…We also note that the small corrections on derived solar Fe abundances from including small scale magnetic fields with no net magnetic flux are not totally negligible in discussions of very precise abundances of solar twins. Shchukina and Trujillo Bueno (2015) found an average correction of +0.016 dex for Fe i lines, but for low-excitation lines formed in the upper photosphere the correction reaches ∼ +0.05 dex. Considering that the magnetic field configuration and strength may vary between solar twins, there could be significant magnetic effects on derived differential abundances.…”
Section: Effects Of Magnetic Fieldsmentioning
confidence: 94%